Student Understanding of The Sales and Collection Cycle Audit through the Web-based Learning Implementation - Rahman, Aulia Fuad; Rusydi, Mohamad Khoiru; Wulandari, Putu Prima; Kholilah, Kholilah; Dewi, Ayu Aryista (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Sumatera Utara, 2024)
The purpose of this study is to compare student understanding levels before and after the implementation of web-based learning. This research is crucial to maintain the focus of learning media development on CLO achievement, which is the core objective of learning. This qualitative study aims to provide descriptive accounts of the findings of variations in students' scores before and after using web-based learning. Thirty students in the Auditing 2 class were subjected to the implementation of learning at one of the leading universities in East Java, Indonesia. The test consisted of six parts, ICQ, confirmation of accounts receivable, subsequent test, test of detail, accounts receivable working paper, and sales working paper related to the sales and collection cycle. The findings indicate that due to students' active involvement in learning, there is a very large increase in the average student score before and after the web-based learning implementation.